Long Non-coding RNA Rhabdomyosarcoma 2-Associated Transcript Regulates Angiogenesis in Endothelial Cells - Alaqeeli, Maha; Mayaki, Dominique; Hussain, Sabah N. A. (Frontiers in Physiology, 2021)
Background: Long non-coding RNAs (lncRNAs) are non-coding RNAs that have more than 200 nucleotides. They have recently emerged as important regulators of angiogenesis. To identify novel lncRNAs that may be involved in the regulation of angiogenesis, we detected mRNA expressions of eighty-four lncRNAs in human umbilical vein endothelial cells (HUVECs) exposed to hypoxia for 24 h. One of these, rhabdomyosarcoma 2-associated transcript (RMST), is significantly upregulated by hypoxia. Little is known about the presence and the role of RMST in EC function. Objective: The main objective of the study is to investigate the regulation of RMST in ECs and to determine its role in in EC survival, proliferation, migration, and differentiation. Methods: Using qPCR, we measured basal mRNA levels of ten RMST isoforms in HUVECs and in response to 24 h hypoxia, seven days of differentiation in co-culture assays, and exposure to four angiogenesis factors. Functional roles of RMST in EC survival, migration, and differentiation were quantified by using a loss-of-function approach (transfection with single-stranded antisense LNA GapmeRs). EC survival was measured by cell counts and crystal violet assays. Cell migration and differentiation were measured with scratch wound healing and Matrigel® differentiation assays, respectively. Results: Five RMST isoforms (RMST-202, -203, -204, -206, and -207) were detected in HUVECs and human microvascular endothelial cells (HMEC-1s). This expression profile was not seen in other vascular cells, including human aortic valve interstitial cells and human aortic smooth muscle cells. RMST was significantly upregulated in response to 24 h of hypoxia and to seven days of co-culture of HUVECs with human lung fibroblasts. RMST was significantly downregulated by angiopoietin-2 (Ang-2) but not by VEGF, FGF-2, or angiopoietin-1 (Ang-1). Selective knockdown of RMST showed that it promotes EC survival in response to serum deprivation. It is also required for VEGF- and Ang-1-induced EC survival and migration but not for differentiation. Conclusions: We conclude that RMST is expressed in human ECs and that this expression is upregulated in response to hypoxia and during differentiation into capillary-like structures. We also conclude that RMST plays important roles in EC survival and migration.